Cyclodextrin modified ionic liquid material as a modifier for cloud point extraction of phenolic compounds using spectrophotometry - Zain, N.N.M.; Raoov, M.; Abu Bakar, N.K.; Mohamad, S. (Springer Verlag (Germany), 2016)
A greener method based on cloud point extraction (CPE) in the presence of b-cyclodextrin (CPE-bCD) and β-cyclodextrin functionalized with ionic liquids (CPE- β CD-IL) systems were investigated and compared for the removal of 2,4,6-TCP and 4-NP in aqueous sample using UV-Vis spectrophotometric method. In the present study, β CD-IL modifier, was used in CPE- β CD-IL system as an enhancement in the removal of 2,4,6-TCP and 4-NP. The removal of 2,4,6-TCP and 4-NP were optimum at pH 7 with concentration of DC193C, 0.5 (v/v %), for this work. Apart from that, the removal process was found to be optimum at 10 mg L-1 of both modifies concentration. For the isotherm study, monolayer solubilization capacity is greater for 2,4,6-TCP than 4-NP. The performance of the β CD-IL modifier towards the hydrophilic 4-NP showed enhanced extraction efficiency in the present study as compared to the β -CD modifier. Finally, the interactions between the cavity of β CD-IL with 4-NP and DC193C were investigated and the results show that the inclusion of the complex formation, hydrogen bonding between DC193C and 4-NP, π- π interaction, electrostatic attraction between the imidazolium ring of the β CD-IL was the main interactions involved in the extraction process.